Slang and socialility : in-group language among college students - Eble, Connie C. (University of North Carolina Press, 1996)
In Slang & Sociability, Eble explores the words and phrases that American college students use casually among themselves. Based on more than 10,000 examples submitted by Eble's students at the University of North Carolina at Chapel Hill over the last twenty years, the book shows that slang is dynamic vocabulary that cannot be dismissed as deviant or marginal. Like more formal words and phrases, slang is created, modified, and transmitted by its users to serve their own purposes.